2023
DOI: 10.3390/rs15041138
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Monitoring of the Pietrafitta Earth Flows in Southern Italy: An Integrated Approach Based on Multi-Sensor Data

Abstract: Earth flows are complex gravitational events characterised by a heterogeneous displacement pattern in terms of scale, style, and orientation. As a result, their monitoring, for both knowledge and emergency purposes, represents a relevant challenge in the field of engineering geology. This paper aims to assess the capabilities, peculiarities, and limitations of different remote sensing monitoring techniques through their application to the Pietrafitta earth flow (Southern Italy). The research compared and combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…of the Campania Region, located 3 km west and at the same elevation as the Pietrafitta earth flow (Figure 2). Pietrafitta's earth flow has been the subject of specific studies, including the work [15], which aimed to study the process through remote sensing instruments and a multi-sensor Pietrafitta's earth flow has been the subject of specific studies, including the work [15], which aimed to study the process through remote sensing instruments and a multi-sensor approach. The work carried out by the authors of [15] took into consideration the period of activity in 2016, exploiting different monitoring systems installed along the slope and combining the results of the different technologies.…”
Section: Pietrafitta Earth Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…of the Campania Region, located 3 km west and at the same elevation as the Pietrafitta earth flow (Figure 2). Pietrafitta's earth flow has been the subject of specific studies, including the work [15], which aimed to study the process through remote sensing instruments and a multi-sensor Pietrafitta's earth flow has been the subject of specific studies, including the work [15], which aimed to study the process through remote sensing instruments and a multi-sensor approach. The work carried out by the authors of [15] took into consideration the period of activity in 2016, exploiting different monitoring systems installed along the slope and combining the results of the different technologies.…”
Section: Pietrafitta Earth Flowmentioning
confidence: 99%
“…Also, the authors of [14] employed a Ground-Based Interferometric Synthetic Aperture Radar (GB-InSAR) for risk management associated with an earth flow reactivation. Instead, the authors of [15] compared and combined data collected during different earth flow phases that occurred in 2016 in the site of Pietrafitta using different ground-based remote sensors such as RTS, GB-InSAR, and Terrestrial Laser Scanners (TLSs), with the aim to derive insights into the performance of such techniques. In addition, the authors of [16] demonstrated the applicability of using global positioning system (GPS) techniques to determine the 3D coordinates of the moving points of an earth flow precisely.…”
Section: Introductionmentioning
confidence: 99%
“…PhotoMonitoring is an innovative monitoring solution that utilizes advanced digital image processing algorithms to harness the extensive utilization of optical/multispectral, hyperspectral, and radar sensors on a global scale [12]. By employing digital image processing techniques, PhotoMonitoring enables the extraction of considerable change information (change detection) and/or analysis of displacement of a target object in two (or more) pictures (digital image correlation) (Figure 2).…”
Section: Remote Sensing Technique (Rts) 231 Principles Of Photomonito...mentioning
confidence: 99%
“…The displacement analysis method implemented in the IRIS software, on the other hand, involves different types of algorithms that exploit different analysis techniques (feature tracking, phase correlation, and an Optical Flow algorithm). Displacement maps can be created through a single pair of images (single analysis approach) or through a stack of images depicting the same area (multi-master approach) [12]. In this second case, the use of a stack of images instead of a single pair allows an advanced application of the DIC technique (multiple-pairwise image matching correlation (MPIC) or multi-master analysis).…”
Section: Principles Of Photomonitoringmentioning
confidence: 99%
See 1 more Smart Citation